2023
DOI: 10.3389/fvets.2023.1063427
|View full text |Cite
|
Sign up to set email alerts
|

Bone quality changes as measured by Raman and FTIR spectroscopy in primiparous cows with humeral fracture from New Zealand

Abstract: The occurrence of spontaneous humeral fractures in primiparous dairy cows from New Zealand prompted the study of bone material from affected cows to further characterize this condition and to outline a likely pathogenesis. Previous studies indicate that these cows developed osteoporosis due to periods of suboptimal bone formation followed by increased bone resorption during the period of lactation complicated by copper deficiency. We hypothesized that there are significant differences in the chemical compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Furthermore, the peak occurrence of humeral fractures in dairy cows appears to coincide with the resumption of cyclicity post-calving, with the increased physical activity due to oestrus behavior likely contributing to fracture occurrence. Recent studies on humeral fractures in New Zealand have reported that the condition is associated with periods of inadequate feed quality, leading to decreased bone formation and increased abnormal bone resorption that severely affects bone quality and strength [9][10][11]37,38]. Some support for this hypothesis is provided by a study in yearling zebu steers where an experimental dietary protein deficiency applied over 100 days resulted in evidence of mild rib osteoporosis, indicating an association with phosphorus and calcium and decreased absorption [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the peak occurrence of humeral fractures in dairy cows appears to coincide with the resumption of cyclicity post-calving, with the increased physical activity due to oestrus behavior likely contributing to fracture occurrence. Recent studies on humeral fractures in New Zealand have reported that the condition is associated with periods of inadequate feed quality, leading to decreased bone formation and increased abnormal bone resorption that severely affects bone quality and strength [9][10][11]37,38]. Some support for this hypothesis is provided by a study in yearling zebu steers where an experimental dietary protein deficiency applied over 100 days resulted in evidence of mild rib osteoporosis, indicating an association with phosphorus and calcium and decreased absorption [39].…”
Section: Discussionmentioning
confidence: 99%